(untitled) (Jurnal Bahasa, 2019)
The research monitors the use of languages among the Malays in Singapore. It aims to identify the role of languages in their pragmatic use in a bilingual environment. Qualitative data were collected through interviews and analysed based on the language use framework. The data were recorded and transcribed using the phonemic transcription technique. Conversations from the interviews were recorded verbatim using standard orthography. Paralinguistic features were also observed and recorded. The research found that the use of Malay in Singapore is polyglossic and diglossic. It also found that the presence of four types of colloquial Malay helps to stabilize the impact of bilingualism in Singapore. The existence of such language variation helps to bring the Malays closer as a community and helps them to preserve their culture and ethnicity. Keywords: bilingualism, language use, language accommodation, colloquial language, domain, diglossia, language vitality